INCESTUOUS RELATIONS ON THE DRAMATIC RADAR OF DATTANI IN THIRTY DAYS HAS SEPTEMBER - Dr. Rajneesh Pandey (Galaxy International Interdisciplinary Research Journal, 2021)
The pivotal point of the play is very well projected, developed and focussed. It loudly heralds all our vaunting of the wonderful past of our country and the so called social, economic and scientific bloom and boom are utterly worthless if we are devoid of the pluck to face and admit the pungent truth of incestuous relations which, regrettably, has become the unseen malignant cancerous cells running in the blood our so called glamorous modern society. It is really very surprising in a country like India where various books on sex like Kamasutra have been written by our great ancient sages centuries ago but that sex is a tabooed subject even in contemporary India. The play shockingly reveals how the crime of incestuous relation is done by the same person who exploits both mother and her daughter Mala. The play also touchingly represents the conflict between mother and daughter which is born out of mother’s silence against her daughter’s molestation.